Walid Jumbaltt’s position on AlJabel war 1982-1984 - Khalaf, Fathi Abbas; AlRawas, Heba Muwafak Younis (Arab Journal for Sciences and Research Publishing, 2022)
Walid Jumblatt played a prominent role on the Lebanese political scene since he entered the political fray in 1977, as he stood by the Palestine Liberation Organization in all periods of the Lebanese civil war 1977-1990. Lebanon, but the situation in the region did not calm down, and the unrest continued until the reign of Walid Jumblatt, with the beginning of the Israeli withdrawal from the mountain in the spring of 1983, Bashir Gemayel announced the entry of the Lebanese forces into the region, and this statement did not meet the approval of Walid Jumblatt, as he opposed the decision and began to control the region and war broke out between the Lebanese army And the Lebanese Forces on the one hand and Walid Jumblatt on the other hand, and the war continued until 1986, after intensive Arab initiatives, the situation was calmed and the war stopped, but despite its stopping, the skirmishes and light disturbances that were taking place from time to time remaine.